Mass concentration of airborne particulates in selected museums at Kuala Lumpur and Perak - Mohd. Din, Shamzani Affendy; Hanapi, Norsyamimi (AMER ABRA cE-Bs bye-International Publishing House Ltd.,UK., 2018)
Indoor pollutants gives harmful effects to human health and became the main cause of the cultural heritage deterioration. The research is focuses on the airborne particulates at the indoor of the museum galleries. Equipment used to sample inhalable dust was the 7-hole sampler and the Cyclone sampler for sample respirable dust. The results show that mass concentrations at selected location were exceeding the limit of safety Indoor Air Quality (IAQ) and Malaysia standard limit for TSP and PM10 in 8 hours sampling. Thus, it is important to control the level of contaminants within the buildings for safety purposes.